¿Limitaciones de género para el desarrollo profesional? mujeres y hombres que participan en la ciencia y la tecnología en la Universidad Nacional de Costa Rica - Palma Campos, Claudia (2010)
This article shows results of a research regarding the scholar work of men and women in the fields of science and technology at the Universidad Nacional. This qualitative analysis research was based on the narratives of female and male scholars interviewed in 2006 and 2007. The objective of this project was to explain and to understand the unequal participation and differences in scientific production between sexes that holds a 35/65 ratio in favor to men. This paper intends to contribute to a process of making sexist practices visible, as means to assess what has been done and what still lays ahead as a necessary step for advancing policies on gender equality at the University. This article marks an end to the series of our research project report on gender-related issues first published on Temas 47 regarding female and male participation in science.